How oral probiotics affect the severity of an experimental model of progressive multiple sclerosis? Bringing commensal bacteria into the neurodegenerative process. Issue 1 (9th November 2020) - Mestre, Leyre; Carrillo-Salinas, Francisco J.; Feliú, Ana; Mecha, Miriam; Alonso, Graciela; Espejo, Carmen; Calvo-Barreiro, Laura; Luque-García, José L.; Estevez, Héctor; Villar, Luisa María; Guaza, Carmen
ABSTRACT: A growing number of studies support that the bidirectional interactions between the gut microbiota, the immune system and the CNS are relevant for the pathophysiology of MS. Several studies have reported alterations in the gut microbiome of MS patients. In addition, a variety of studies in animal models of MS have suggested that specific members of the gut commensal microbiota can exacerbate or ameliorate neuroinflammation. Probiotics represent oral nontoxic immunomodulatory agents that would exert benefits when using in combination with current MS therapy. Here we investigate the effect of Vivomixx on the gut microbiome and central and peripheral immune responses in a murine model of primary progressive MS. Vivomixx administration was associated with increased abundance of many taxa such as Bacteroidetes, Actinobacteria, Tenericutes and TM7 . This was accompanied by a clear improvement of the motor disability of Theiler's virus infected mice; in the CNS Vivomixx reduced microgliosis, astrogliosis and leukocyte infiltration. Notably, the presence of Breg cells (CD19 + CD5 + CD1d high ) in the CNS was enhanced by Vivomixx, and while spinal cord gene expression of IL-1β and IL-6 was diminished, the probiotic promoted IL-10 gene expression. One of the most significant findings was the increased plasma levels of butyrate and acetate levels in TMEV-mice that received Vivomixx. Peripheral immunological changes were subtle but interestingly, the probiotic restricted IL-17 production by Th17-polarized CD4 + T-cells purified from the mesenteric lymph nodes of Theiler's virus infected mice. Our data reinforce the beneficial effects of oral probiotics that would be coadjuvant treatments to current MS therapies.